2022
DOI: 10.1111/myc.13425
|View full text |Cite
|
Sign up to set email alerts
|

Changing face of epidemiology of dermatophytoses in Chinese Mainland: A 30 years nationwide retrospective study from 1991 to 2020

Abstract: Dermatophytoses, the most common fungal infections worldwide, caused by dermatophytes, mainly including Trichophyton (T.) genus, Microsporum (M.) genus and Epidermophyton (E.) genus, affect hundreds of millions of people. 1 Dermatophyte infections are clinically referred as 'tinea' or 'ringworm', which can be divided, based on the different infection sites, into tinea manuum (hands), tinea pedis (feet), tinea corporis (trunk and limbs), tinea cruris (inguinal-crural region), tinea capitis (scalp and hair) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The prevalence and causative agents of tinea faciei vary across regions. The reported isolation rates range from 0.4% to 4.2% in various parts of the world [ 16 , 17 , 18 , 19 , 20 , 21 , 26 , 36 , 37 , 38 , 39 , 40 , 58 , 59 ], with more than 50% of cases observed in patients younger than 12 years of age [ 37 , 60 ]. In Europe, a study conducted in Portugal identified M. audouinii , T. soudanense , and T. rubrum as the main pathogenic agents [ 60 ].…”
Section: Body Sites Dermatophyte Species and Their Geographical Distr...mentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence and causative agents of tinea faciei vary across regions. The reported isolation rates range from 0.4% to 4.2% in various parts of the world [ 16 , 17 , 18 , 19 , 20 , 21 , 26 , 36 , 37 , 38 , 39 , 40 , 58 , 59 ], with more than 50% of cases observed in patients younger than 12 years of age [ 37 , 60 ]. In Europe, a study conducted in Portugal identified M. audouinii , T. soudanense , and T. rubrum as the main pathogenic agents [ 60 ].…”
Section: Body Sites Dermatophyte Species and Their Geographical Distr...mentioning
confidence: 99%
“…In Africa, the estimated prevalence ranges from 2% to 41% [ 3 ]. In other regions, the prevalence of tinea corporis among isolated dermatophytes is estimated to be between 2.8% and 30.3% ( Table 2 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 26 , 36 , 37 , 38 , 39 , 40 , 58 , 59 ]. Notably, in India, there has been a shift in prevalence over the past two decades, with T. mentagrophytes emerging as a replacement for T. rubrum [ 27 , 68 ].…”
Section: Body Sites Dermatophyte Species and Their Geographical Distr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dermatophytes is the most common fungal disorders, affecting about 20-25% of the world's population and the prevalence is increasing [1,2]. Trichophyton mentagrophytes have replaced T. rubrum infections in frequency, especially in India [1].…”
Section: Introductionmentioning
confidence: 99%
“…Dermatophytosis is the most common superficial mycosis worldwide 1,2 . In the past few years, the number of recalcitrant and extensive tinea corporis and tinea cruris caused by Trichophyton mentagrophytes complex, recently named as T. indotineae , has been sharply increased, 3 form pandemic India 4 to other countries, such as Iran, 5 German, 6 Japan, 7 France, 8 Canada, 9 Turkey 10 and China 11 .…”
Section: Introductionmentioning
confidence: 99%